An Appraisal of Anaesthesia for Ectopic Pregnancy in a Tertiary Institution North-Central Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Ectopic pregnancy is a life threatening gynaecological emergency; it is a significant cause of maternal morbidity and mortality, thus poses various anaesthetic challenges.Aims:To determine the profile of women that present with ectopic gestation, their mode of presentation, the anaesthetic technique used, complications and outcome.Settings and Design:This was a retrospective review of ectopic pregnancy at the University of Ilorin teaching hospital from 1stJanuary 2015 to 31stDecember 2018.Materials and Methods:Data were obtained from operating theatre records, anaesthetic records regarding modes of anaesthesia, complications and outcomes were extracted.Statistical analysis used:Analysis was done IBM SPSS version 22.Results:There were 89 cases of ectopic pregnancies that were managed during the period of review. The incidence of ectopic pregnancy in this study was 0.9% of all deliveries. A total of 69 (77.5%) of the case file were available and were retrieved and analysed. The age range was 25–29 years, with mean age of 27.5 ± 5.4 years. Most of the patients presented with ruptured ectopic 57 (82.6%). All the patients had general anaesthesia, and ketamine 47 (68.2%) was the predominant induction agent (P= 0.007). The most common surgical intervention performed was open laparotomy with unilateral salpingectomy 60 (87%). Fifty three (76.8%) of the patients required intra operative blood transfusion. All patients with the American Society of Aanesthesiologists (ASA) IVE had ruptured ectopic, while 88% of patients with ASA IIIE presented with ruptured ectopic. Ninety per cent of the patient that were ASA IVE had an immediate post operative complication. While the least complication was seen in patients with ASA IE 3 (37.5%). No patient required intensive care admission, and no mortality was recorded.Conclusion:The most common form of presentation of ectopic pregnancy in this study was ruptured unilateral ectopic, and general anaesthesia for laparotomy was the most common intervention.